Notes on infinite-dimensional nonlinear parabolic equations - Feller, M. N. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We present a method for the solution of the Cauchy problem for three broad classes of nonlinear parabolic equations U( t,x ) t = f( Δ _L U( t,x ) ), U( t,x ) t f( t,Δ _L U( t,x ) ), and U( t,x ) t = f( U( t,x ), Δ _L U( t,x ) ) with the infinite-dimensional Laplacian ΔL.